Understanding the compliance of patients with hand injuries in South Africa: a quantitative study of occupational therapists’ views - Makhlouf, Emily (My University, 2022)
Background: Patient compliance has been reported to have a substantial impact on hand rehabilitation outcomes in South Africa. In a low to middle-income country (LMIC), where a hand injury may cost a patient their livelihood, it is essential to develop local evidence to support patient compliance. This study aimed to describe how South African occupational therapists understand the compliance of hand-injured patients and their perceptions of the factors affecting, and strategies, used to facilitate patient compliance. Method: A descriptive quantitative cross-sectional survey was employed. The online survey questionnaire was based on a review of the literature and its content validity was strengthened through expert review and refinement. Descriptive statistics and quantitative content analysis were employed. Results: A response rate of 52.7% (n=99) was achieved. Participants who work in the private (48.5%) and public (46.5%) health sectors were represented. Most of the participants (61.2%) believed ‘compliance’ to be the most appropriate term. Socioeconomic and healthcare system/team-related factors were more frequently perceived to influence compliance than condition, therapy, and patient-related factors. However, the latter factors were more frequently targeted for intervention by therapists and their respective departments/practices. Conclusion: Participants continue to prefer the use of the term ‘compliance’ despite literature dissuading this. Several socio-economic and healthcare system/teamrelated factors were identified, and therapy-related strategies were recommended. It is recommended that a collaborative workshop with South African occupational therapists be used to discuss results and collectively formulate realistic avenues for action.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Occupational Therapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, 2022